Disfunción eréctil: factor predictor de enfermedad cardiovascular - Brito Ferrer, Yudileidy; Árias Gallardo, Ana I.; González Caballero, Yossy (CorSalud, 2013)
Disfunción eréctil: factor predictor de enfermedad cardiovascular